2013
DOI: 10.1002/lt.23659
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Incidence of Symptomatic Epstein-Barr Virus Disease and Posttransplant Lymphoproliferative Disorder in Pediatric Liver Transplant Recipients: Report of the Studies of Pediatric Liver Transplantation Experience

Abstract: Post transplant lymphoproliferative disorder (PTLD) causes significant morbidity and mortality in pediatric recipients of liver transplantation (LT). Objective Describe the incidence of PTLD and symptomatic Epstein Barr virus disease (SEBV) in a large multicenter cohort of children who have undergone LT focused on the risk factors and changes in incidence over time. Methods Prospective determination of SEBV and PTLD in 2283 subjects who had undergone a first LT with at least 1 year of follow up in the Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 21 publications
5
80
2
2
Order By: Relevance
“…For early detection and furthermore prevention of PTLD, monitoring EBV viral load is considered as one of the crucial factors, even though the specificity and positive predictive value of EBV titer in predicting PTLD are still controversial24252627). As an example, right after that regular EBV viral load monitoring was adopted as standard clinical practice, our center encountered only one case of pediatric PTLD during 2008–2012; Upon recognition of high titer of EBV of >10,000 copies/mL immunosuppression was reduced when possible, and active surveillance of PTLD was adopted.…”
Section: Discussionmentioning
confidence: 99%
“…For early detection and furthermore prevention of PTLD, monitoring EBV viral load is considered as one of the crucial factors, even though the specificity and positive predictive value of EBV titer in predicting PTLD are still controversial24252627). As an example, right after that regular EBV viral load monitoring was adopted as standard clinical practice, our center encountered only one case of pediatric PTLD during 2008–2012; Upon recognition of high titer of EBV of >10,000 copies/mL immunosuppression was reduced when possible, and active surveillance of PTLD was adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, of those patients who developed posttransplant lymphoproliferative disease, all but 1 patient in each group were positive for Epstein-Barr virus at the time of transplant. Among the risks factors associated with posttransplant lymphoproliferative disease after liver transplant, Narkewicz and associates 18 found that ACR is associated with increased risk of posttransplant lymphoproliferative disease, likely due to the increased amount of immunosuppression that has to be administered. With the use of rATG, we demonstrated a significantly decreased rate of ACR, which could explain the lower incidence of posttransplant lymphoproliferative disease in this group.…”
Section: Discussionmentioning
confidence: 99%
“…The primary risk factors for PTLD are recipient EBV‐naïve status, higher levels of immunosuppression, type of allograft, and recipient's age . The risk of developing PTLD is reported to be intermediate (1%‐12%) in liver transplantation among all SOTs due to lower levels of immunosuppression required and less amount of lymphoid tissue involved .…”
Section: Discussionmentioning
confidence: 99%